Catalyzed Ester Synthesis Using Candida rugosa Lipase Entrapped by Poly(N-isopropylacrylamide-co-itaconic Acid) Hydrogel - Nikola Milašinović; Sonja Jakovetić; Zorica Knežević-Jugović; Nedeljko Milosavljević; Marija Lučić; Jovanka Filipović; Melina Kalagasidis Krušić (The Scientific World Journal)
This study reports the synthesis of polymeric matrices based on N-isopropylacrylamide and itaconic acid and its application for immobilization of lipase from Candida rugosa. The lipase was immobilized by entrapment method. Free and immobilized lipase activities, pH and temperature optima, and storage stability were investigated. The optimum temperature for free and entrapped lipase was found to be 40 and 45°C, while the optimum pH was observed at pH 7 and 8, respectively. Both hydrolytic activity in an aqueous medium and esterolytic activity in an organic medium have been evaluated. Maximum reaction rate (Vmax) and Michaelis-Menten constants (Km) were also determined for immobilized lipase. Storage stability of lipase was increased as a result of immobilization process. Furthermore, the operational stability and reusability of the immobilized lipase in esterification reaction have been studied, and it was observed that after 10 cycles, the residual activity for entrapped lipase was as high as 50%, implying that the developed hydrogel and immobilized system could provide a promising solution for the flavor ester synthesis at the industrial scale.